2019
DOI: 10.1101/683029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity in natural transformation frequencies and regulation acrossVibriospecies

Abstract: 24In marine Vibrio species, chitin-induced natural transformation enables bacteria to take up DNA 25 from the external environment and integrate it into their genome via homologous recombination. 26Expression of the master competence regulator TfoX bypasses the need for chitin induction and 27 drives expression of the genes required for competence in several Vibrio species. Here, we 28 show that TfoX expression in two Vibrio campbellii strains, DS40M4 and NBRC 15631, enables 29 high frequencies of natural tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…To determine whether homologs of previously tested BB120 quorum-sensing sRNAs and proteins have similar functions in DS40M4, we generated numerous mutant strains, including Δ cqsA , Δ luxS , Δ cqsA Δ luxS , Δ luxO , Δ luxR, luxO D47E (a LuxO phosphomimic allele), in addition to every combination of qrr deletion (single or combined). We previously showed, using a P luxCDABE -gfp reporter plasmid, that wild-type DS40M4 activates the luxCDABE promoter from BB120, and this is dependent on DS40M4 LuxR (15). We have since constructed a plasmid encoding the BB120 luxCDABE operon under control of its endogenous promoter (pCS38) for use in DS40M4, which enables us to monitor bioluminescence of various DS40M4 strains and assess LuxR regulation as a function of upstream quorum-sensing components.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether homologs of previously tested BB120 quorum-sensing sRNAs and proteins have similar functions in DS40M4, we generated numerous mutant strains, including Δ cqsA , Δ luxS , Δ cqsA Δ luxS , Δ luxO , Δ luxR, luxO D47E (a LuxO phosphomimic allele), in addition to every combination of qrr deletion (single or combined). We previously showed, using a P luxCDABE -gfp reporter plasmid, that wild-type DS40M4 activates the luxCDABE promoter from BB120, and this is dependent on DS40M4 LuxR (15). We have since constructed a plasmid encoding the BB120 luxCDABE operon under control of its endogenous promoter (pCS38) for use in DS40M4, which enables us to monitor bioluminescence of various DS40M4 strains and assess LuxR regulation as a function of upstream quorum-sensing components.…”
Section: Resultsmentioning
confidence: 99%
“…We previously assessed the molecules sensed by DS40M4 receptors CqsS and LuxPQ (15). Our data showed that DS40M4 senses the AI-2 and CAI-1 molecules produced by BB120 but not BB120 HAI-1, even though DS40M4 encodes a LuxN homolog.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations